2006
DOI: 10.1083/jcb.200607061
|View full text |Cite
|
Sign up to set email alerts
|

Defective mitochondrial peroxiredoxin-3 results in sensitivity to oxidative stress in Fanconi anemia

Abstract: Cells from patients with Fanconi anemia (FA), an inherited disorder that includes bone marrow failure and cancer predisposition, have increased sensitivity to oxidative stress through an unknown mechanism. We demonstrate that the FA group G (FANCG) protein is found in mitochondria. Wild-type but not G546R mutant FANCG physically interacts with the mitochondrial peroxidase peroxiredoxin-3 (PRDX3). PRDX3 is deregulated in FA cells, including cleavage by a calpainlike cysteine protease and mislocalization. FA-G c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 55 publications
6
104
0
Order By: Relevance
“…Nonn et al (35) overexpressed PRx-3 in WEHI7.2 thymoma cells and found that this overexpression led to decreased levels of cellular H 2 O 2 and that it protected these cells from H 2 O 2 -induced apoptosis. Similarly, Mukhopadhyay et al (34) studied PRx-3 in different cell lines in patients with Fanconi's Anemia (FA). They found that these cells, among other things, had a sevenfold decrease in PRx-3 expression compared with WT control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nonn et al (35) overexpressed PRx-3 in WEHI7.2 thymoma cells and found that this overexpression led to decreased levels of cellular H 2 O 2 and that it protected these cells from H 2 O 2 -induced apoptosis. Similarly, Mukhopadhyay et al (34) studied PRx-3 in different cell lines in patients with Fanconi's Anemia (FA). They found that these cells, among other things, had a sevenfold decrease in PRx-3 expression compared with WT control cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both Prx3 and Prx6 are inactivated after over-oxidation of the catalytic cysteine residue and are the slowest Prx isoforms to be reductively reactivated (34,35). In addition, Prx3 has been shown to be cleaved and inactivated by a calpain-like cysteine protease after oxidant treatment in lymphoblasts (33). Importantly, Prxs are more Several studies have shown that overexpression of Prxs can protect neurons from various forms of toxic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Prx activity is regulated by post-translational modifications including oxidation (sulfinylation/sulfonylation), phosphorylation, and proteolytic cleavage (11,32,33). Both control and A␤-treated PC12 cells expressed increased levels of both high and low molecular weight acidic Prx3 and Prx6 isoforms as compared with the A␤-resistant line (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…39 In addition, FANCG interacts with cytochrome P450 2E1, which is associated with the production of reactive oxygen intermediates, and the mitochondrial antioxidant enzyme peroxiredoxin-3. 40,41 Finally, we recently reported that FANCD2 associated with FOXO3a, a master regulator of oxidative stress response. 42 Although these observations point to the involvement of FA proteins in oxidative stress response, the molecular mechanism by which FA proteins function to modulate oxidative stress response has not been defined.…”
mentioning
confidence: 99%